Arketipe dalam Novel Re: Karya Maman Suherman: Analisis Psikologi Analitik Carl Gustav Jung - Andi Widian Prabowo; I Wayan Cika; I G.A.A. Mas Triadnyani (Udayana University, 2023)
The world of prostitution is not solely caused by the abyss of poverty. However, it is caused by the turmoil of the human unconscious on the causality of his personality. Re is the main character in the novel Re by Maman Suherman who represents the complex world of playing games. The arena that Re is involved in, featuring various interesting characters is reviewed in more depth. Problems in tracing the personality of the characters in Maman Suherman's novel Re. The theory used is Carl Gustav Jung's Psychoanalysis. Data was collected using a literature study method with reading, listening, and note-taking techniques. Data analysis was carried out by interpretive descriptive method. The results are based on research, the incident utilizes the background as the main strength with detailed specifications. The whole is not fully interwoven in the relationship between elements. The psychological character of Re displays the archetype of the audience, the great mother, and the hero which is manifested in her psychic causality. The character of Re shows the personality of the collective unconscious (persona, shadow, anima and animus), Herman reflects the persona of an intelligent student, and Mami Lani is a representation of the persona of a blind heart.